(3THcGJ GdEYdGe (B/s - (3EjQjS,CfWhGf s; (3TGgjf(B,(3aDGOs ((3dHfGf (B:s (3YhjOGJ ddfTQ h GdWHGYI ,s, 2001)
(3jTcd gPG GdcJGH eONdG MbjbjG dYGde GdEYdGe h GdGJUGdGJ h HSHM VQhQjG djS abW ddENJUGUjjf Hd MJi ddehGWfjf GdYGOjjf h NGUI ddPjf dG jRGdhf jbGhehf GdGfJbGd Gdi eLJeY GdEYdGe eYJHQjf Pdc fhYG ef GdJQa h djS MGLI aYdjjfs
Keywords: (3JcfhdhLjG GdeYdheGJs; (3THcGJ GdGJUGd s